1999
DOI: 10.1002/(sici)1097-0274(199903)35:3<264::aid-ajim6>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated mortality from nonalcohol-related chronic liver disease among female rubber workers: Is it associated with exposure to nitrosamines?

Abstract: Background Despite several case reports describing liver toxicity of nitrosamines and the fact that some N‐nitroso compounds are used to induce cirrhosis of the liver in animal models, this association has not been investigated in epidemiological studies. Methods A cohort of 2,875 female rubber workers who were active on January 1, 1976, or hired thereafter, and who had been employed for at least 1 year in one of five plants producing tires or technical rubber goods was followed for mortality from January, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Occupational exposure to chemicals has been identi®ed as being possibly associated with the occurrence of liver cirrhosis [Dùssing and Skinhùj, 1985]. The California mortality study data set showed the highest mortality rates from liver cirrhosis among construction workers and machinists [Harford and Brooks, 1992] and female rubber workers [Straif et al, 1999]. In addition, with respect to the potential role of viral infections in the etiology of liver cancer and cirrhosis, it is unlikely that the proportion of shipyard workers exposed to viral agents differs from that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure to chemicals has been identi®ed as being possibly associated with the occurrence of liver cirrhosis [Dùssing and Skinhùj, 1985]. The California mortality study data set showed the highest mortality rates from liver cirrhosis among construction workers and machinists [Harford and Brooks, 1992] and female rubber workers [Straif et al, 1999]. In addition, with respect to the potential role of viral infections in the etiology of liver cancer and cirrhosis, it is unlikely that the proportion of shipyard workers exposed to viral agents differs from that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Dimethylnitrosamine is a hepatocarcinogen and hepatotoxicant commonly employed for the induction of experimental liver fibrosis. A recent study revealed that the liver cirrhosis induced by the drug in animal models appeared to parallel with the results of epidemiological studies (Straif et al 1999). Dimethylnitrosamine is toxic to hepatocytes through bioactivation and induces coagulative necrosis in the centrilobular and periportal areas in the liver.…”
Section: Discussionmentioning
confidence: 82%
“…Epidemiological studies have shown that rubber workers died excessively from liver cirrhosis, which might be associated with the occupational risk factors such as exposure to N-nitroso compounds (Straif et al 1999). Case reports and animal data raised the possibility that exposure to nitrosamines may be a risk factor for incidence of liver cirrhosis and the resultant mortality (Chao et al 1995;Park & Mirer 1996;Straif et al 1999). Nitrosamine, in particular dimethylnitrosamine, is bioactivated by the catalysis of Author for correspondence: Sang Geon Kim, College of Pharmacy, Seoul National University, Sillim-dong, Kwanak-gu, Seoul 151-742, Korea (fax π822 872 1795, e-mail sgk/snu.ac.kr).…”
mentioning
confidence: 99%
“… 10 NDMA was also linked to hepatic adverse outcomes in humans after several poisoning incidents 11 , 12 , 13 and was associated with higher excess mortality from nonalcoholic‐related chronic liver disease after occupational exposure. 14 …”
Section: Clinical Perspectivementioning
confidence: 99%